Radioactividad natural y estado funcional del aparato cutáneo en Bufo Spinulosus wiegmann - Cei, José Miguel Alfredo María (1965)
Samples of dried skins of Bufo spinulosus from the Southern Territories of Mendoza Province (Argentina) have been studied by paper chromatography and the content of biogenic indolalkylamines was measured. Specific aminic spectrum of Bufo spinulosus shows a very low content of 5HT besides a limited quantity of Bufotenine and Bufotenidine, but greater amounts of Dehydrobufotenine and Bufothionine were pointed out. Comparison between samples from a strongly radiactive area (uraniferous ground neighbouring the Minas Huemul mines) and samples from a non-radiactive region (Bardas Blancas, Rio Grande River, South of Minas Huemul) indicates some statistically significative differences in the Bufothionine and 5-HT contents of the skin. At a lesser extent a lowered level of Bufotenidine in the Minas Huemul samples may be stressed. A discussion on the natural factors as soil radiation acting on the enzymatic chaines determining the aminic content of the skin was carried out.